An overview of nanobots in endodontics - Abdulmoeen Alsharif, Ainaa; Assiri, Mohammad Yahya; Alsurayyi, Faris Tariq; Alsanad, Areej Ayedh; Alhamadi, Abrar Abdulrahman; Alqahtani, Nwaf Mohammad (International Journal Of Community Medicine And Public Health, 2025)
Nanorobots are emerging as a transformative technology in endodontics, with the potential to enhance the precision, efficacy, and overall success of root canal treatments. These microscopic devices are capable of navigating the intricate architecture of root canals, identifying and eliminating microbial pathogens, and delivering targeted therapeutic agents with high specificity. By accessing areas that conventional endodontic instruments cannot reach, nanorobots may facilitate more thorough decontamination and reduce the risk of reinfection. Current research focuses on optimizing their biocompatibility, structural integrity, and controllability to ensure both safety and effectiveness in clinical applications. However, several challenges must be addressed before nanorobots can be integrated into routine dental practice. These include high production costs, technical limitations, and the necessity of regulatory approval to ensure their clinical viability. To overcome these barriers, researchers are exploring advanced strategies such as magnetic field navigation, computer-assisted control, and the development of biodegradable nanobots capable of self-dissolution upon task completion. With continued technological advancements, nanorobots have the potential to revolutionize endodontic treatment by offering minimally invasive, highly targeted interventions that enhance procedural success rates and patient recovery. Their autonomous functionality may also reduce reliance on conventional endodontic instruments, thereby reshaping current treatment methodologies. As the field progresses, interdisciplinary collaboration among scientists, engineers, and dental professionals remains essential to addressing existing limitations and facilitating the transition of nanorobots from experimental models to standardized clinical use. This review examines recent developments in nanorobotics, evaluates their advantages and limitations, and discusses their prospective role in the future of root canal therapy.